Characterization methods in porous materials for the rational design of multi-step processing in the context of a paper microfluidic phenylalanine test. Issue 6 (23rd January 2020) - Wentland, Lael; Polaski, Rachel; Fu, Elain
Abstract : We present an example of rational device design in the context of an improved paper microfluidic phenylalanine detection device using detailed characterization of fluid and reagent interactions within the device. Abstract : A promising application of paper microfluidics is the translation of gold-standard multi-step laboratory tests to a disposable paper-based format for decentralized diagnostic or therapeutic testing. This often entails conversion of bench-top processing of macro-volume samples to the processing of micro-volume samples within a porous matrix, and requires detailed characterization of fluid and reagent interactions within the porous material(s) of the device. The current study focuses on rational device design through the characterization of fluid and reagent interactions in polysulfone and glass fiber substrates for multi-step sample processing. Specifically, we demonstrate how the characterization of fluidic compatibility between substrates, chemical compatibility between reagents and substrates, sample pH, and sample transport can be used to inform device design in the context of a two-reaction detection scheme for phenylalanine in porous materials. Finally, we demonstrate detection of phenylalanine from human whole blood, and discuss the multiple strengths of the current design over a previous version.